Single ChAdOx1 nCoV‐19 dose elicits stronger immune response in previously infected individuals than in SARS‐CoV2 naive persons - Fawzi Ebrahim; Asma Alboueishi; Inas M. Alhudiri; Salah Al Tabal; Yosra Lamami; Samira Al Dwigen; Sondos Ashleb; Noha Ejenfawi; Mohamed B. Milad; Hayat Rhoumah; Salah Edin El Meshri; Adam Elzagheid (Immunity, Inflammation and Disease)
Abstract Background Current vaccines against COVID‐19 effectively reduce morbidity and mortality and are vitally important for controlling the pandemic. Between December 2020 and February 2021, adenoviral vector vaccines such as ChAdOx1 (AstraZeneca‐Oxford) were put in use. Recent reports demonstrate robust serological responses to a single dose of messenger RNA vaccines in individuals previously infected with SARS‐CoV‐2. We aimed to study the association between previous COVID‐19 infection and antibody levels after a single dose of ChAdOx1 nCoV‐19. Methods This cross‐sectional study was conducted on 657 individuals who were either convalescent or SARS‐CoV‐2 naive and had received one dose of ChAdOx1 (AstraZeneca). A questionnaire was used to collect data on age, sex, and self‐reported history of COVID‐19 infection. We then compared the average levels of immunoglobulin G (IgG) between the previously infected and COVID‐19‐naive participants. Results We compared the antibody responses of individuals with confirmed prior COVID‐19 infection with those of individuals without prior evidence of infection. The mean antibody levels in those who reported no history of COVID‐19 infection were substantially lower than in those who were previously infected, in both males and females. Sex‐related differences were observed when we compared antibody levels between men and women. In males, anti‐S IgG antibody levels were higher in those who had been previously infected (156.1 vs. 87.69 AU/mL, p = .009), compared with the same pattern was observed in females (113.5 vs. 90.69 AU/mL, p = .005). Conclusions Previous COVID‐19 infection is associated with higher levels of SARS‐CoV‐2 antibodies following ChAdOx1 (AstraZeneca) vaccination. Our finding supports the notion that a single dose of ChAdOx1 nCoV‐19 administered post‐SARS‐CoV‐2 infection serves as an effective immune booster. This provides a possible rationale for a single‐dose vaccine regimen for previously infected individuals.